THE IMPLEMENTATION OF LOVE-BASED ISLAMIC EDUCATION CURRICULUM IN SHAPING STUDENT CHARACTER AT SABILINA TEMBUNG PRIVATE JUNIOR HIGH SCHOOL - Suyono; Bahtiar Siregar; Zikriya Husna Aulia Putri; Aulia Ramadhani Lubis (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the implementation of the Love-Based Islamic Education Curriculum in shaping students' character at Sabilina Tembung Private Junior High School. The research employs a qualitative approach with an exploratory case study design, focusing on the subjective experiences of both Islamic Education teachers and students regarding the application of love-based values in Islamic Education. Data were collected through semi-structured interviews, classroom observations, and document analysis, involving Islamic Education teachers and students from various grade levels. The findings indicate that the Love-Based Islamic Education Curriculum significantly enhances students' discipline, empathy, and social interaction. Storytelling and self-reflection methods were found to be effective in helping students internalize the values of love towards Allah, the Prophet, fellow humans, and nature. However, key challenges identified include the limited availability of relevant teaching materials and students' difficulties in applying love values outside the classroom. The study also highlights the importance of parental and community involvement in supporting the implementation of the Love-Based Islamic Education Curriculum beyond the school environment. The research recommends the development of more applicable teaching materials, ongoing teacher training, and stronger collaboration with parents to reinforce the values of love in students' daily lives. This study contributes significantly to the development of love-based curricula in Indonesian private schools.